LABORATORY PERFORMANCE OF HOT ROLLED ASPHALT CONTAINING CRUSHED BURNT CLAY (BATU BATA) AS A FILLER - Yasrudin
Hot Rolled Asphalt (HRA) is a gap-graded bituminous mixture whose strength derives mainly from the mortar of fine aggregate, filler and bitumen. Mixtures of this type are frequently used in the pavement wearing course in Indonesia because of their relatively high flexibility and durability. The filler is an important component of the HRA mortar and Portland cement is a material that is frequently used for the this purpose. However it is not easily available in some areas of Indonesia and the cost is relatively high. The research described in this thesis was concerned with an evaluation of the suitability of filler produced from traditionaly-burnt clay (batu Bata) as a component of HRA mixtures. Mixtures were designed by the Marshall method for various combinations of batu bata (BB) and crushed rock (CR) filler. The two fillers were combined in the following proportions by weight (BB/CR); 100/0, 80/20, 60/40, 40/60, 20/80 and 0/100. At optimun bitumen content, mix design criteria given in the British Standard specification for HRA were satisfied by all filler combinations; optimum bitumen content reduced as the proportion of CR filler increased. All mixtures had adequate resistance to water damage as indicated by the Index of Retained Stability (IRS) ; this parameter increased with reduction in the proportion of BB filler. In general, Indirect Tensile Strength was not influenced significantly by the filler composition. Resistance to permanent deformation, as indicated by the wheel Tracking Test, was lowest for the mixture containing 100 %o BB filler and improved as the proportion of BB filler in the combination was reduced. Overall the test data suggest that a satisfactory HRA mixture can be produced using BB filler. However further investigation is needed, to determine in particular if there is a tendency for the BB filler to swell when exposed to water for long periods .